2014
DOI: 10.1111/jam.12548
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial effect of Dinoponera quadriceps (Hymenoptera: Formicidae) venom against Staphylococcus aureus strains

Abstract: Aims: Dinoponera quadriceps venom (DqV) was examined to evaluate the antibacterial activity and its bactericidal action mechanism against Staphylococcus aureus. Methods and Results: DqV was tested against a standard strain of methicillinsensitive Staphylococcus aureus (MSSA), Staph. aureus ATCC 6538P and two standard strains of methicillin-resistant Staphylococcus aureus (MRSA), Staph. aureus ATCC 33591 and Staph. aureus CCBH 5330. The minimum inhibitory concentration (MIC) and minimum bactericidal concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 41 publications
0
15
0
2
Order By: Relevance
“…The following human pathogens were used in this work: Pseudomonas aeruginosa PA01 (Alonso et al 1999), Staphylococcus aureus 6538P (Lima et al 2014), Klebsiella pneumoniae DF12SA (Shahi et al 2013), Acinetobacter baumannii Ab13 (Poirel et al 2008), Burkholderia cenocepacia LMG 16656 and Burkholderia metallica LMG 24068 (Soriano et al 2009). The strains were routinely grown at 37°C in LB medium.…”
Section: Pathogenic Strainsmentioning
confidence: 99%
“…The following human pathogens were used in this work: Pseudomonas aeruginosa PA01 (Alonso et al 1999), Staphylococcus aureus 6538P (Lima et al 2014), Klebsiella pneumoniae DF12SA (Shahi et al 2013), Acinetobacter baumannii Ab13 (Poirel et al 2008), Burkholderia cenocepacia LMG 16656 and Burkholderia metallica LMG 24068 (Soriano et al 2009). The strains were routinely grown at 37°C in LB medium.…”
Section: Pathogenic Strainsmentioning
confidence: 99%
“…Some examples of these peptides are ponericins from the predatory ant Pachycondyla goeldii (reclassified as Neoponera goeldii ) [12,13], dinoponeratoxins from the giant neotropical hunting ant Dinoponera australis [14] or bicarinalin from the ant Tetramorium bicarinatum [15]. Such compounds are frequently entitled as antimicrobial peptides (AMPs) due to their activity against a broad spectrum of pathogens, especially bacteria [12,15,16,17,18]. In addition to antimicrobial activity, these linear peptides, even if they belong to the same structural family can display different activities such as cytolytic, hemolytic, and insecticidal activity [3,8].…”
Section: Introductionmentioning
confidence: 99%
“…Cologna et al [ 25 ] evaluated the antimicrobial activity of four peptides from the venom, and two of them showed activity against Gram-positive and -negative bacteria. Corroborating those data, Lima et al [ 67 ] reported the antimicrobial activity of the crude venom against methicillin-sensitive and resistant Staphylococcus aureus strains. The same researchers also reported the antiparasitic effects of the venom against Leishmania amazonensis and Trypanosoma cruzi [ 68 ].…”
Section: Discussionmentioning
confidence: 92%